An iterative frequency-domain decision feedback receiver for CDMA systems - Silva, Paulo (2013)
Unless high-complexity receiver structures are employed, conventional DS-CDMA (direct sequence code division multiple access) schemes can have a poor performance in severe time-dispersive channels, since the orthogonality between the users is lost. In this paper, we propose an iterative frequency-domain decision feedback equalizer for the downlink transmission within DS-CDMA systems employing block-transmission techniques, with an appropriate cyclic extension appended to each block. Our performance results show that the proposed receiver structure has excellent performance, close to the single-user MFB (matched filter bound), even for severe time-dispersive scenarios and/or in the presence of strong interfering channels.